2016
DOI: 10.1016/j.coph.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ as therapeutic targets in cancer

Abstract: The biology and regulation of YAP and TAZ, two closely related transcriptional regulators, are receiving increasing attention owing to their fundamental roles in organ growth, tissue repair and cancer. In particular, the widespread activation of YAP/TAZ in carcinomas, and the crucial role of YAP/TAZ activation for many 'hallmarks' of cancer are indicating YAP/TAZ as prime targets for designing anti-cancer drugs. Here, we start from the known modalities to regulate YAP/TAZ to highlight possible routes of therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(174 citation statements)
references
References 65 publications
2
172
0
Order By: Relevance
“…And it plays a pivotal role in organ size control and tumor suppression by restricting proliferation and promoting apoptosis [15,17]. Similarly to TGFBR2, most research concerning YAP-1 has been carried out within tumor cells; the roles of YAP-1 in immune cells were relatively poorly known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And it plays a pivotal role in organ size control and tumor suppression by restricting proliferation and promoting apoptosis [15,17]. Similarly to TGFBR2, most research concerning YAP-1 has been carried out within tumor cells; the roles of YAP-1 in immune cells were relatively poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…Since YAP is a co-activator of TEADs and has no DNA binding site, its regulation on TGFBR2 is TEADs dependent [17]. A TEADs binding site "GGAATG" was detected in the promoter region of TGFBR2 (Fig.…”
Section: Up-regulation Of Tgfbr2 In T Cells Depends On Yap-1/teads Atmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that F-actin promotes YAP nuclear translocation and inhibits the Hippo pathway, and that destabilization of F-actin results in the nuclear exportation of YAP (32,33). The clinical use of anti-cytoskeletal therapies has been limited due to toxicity (34). Current therapeutic approaches to target mechanotransduction signals in cancer work through inhibiting Rho-associated kinase (ROCK) signaling (34,35).…”
Section: Rockmentioning
confidence: 99%
“…The clinical use of anti-cytoskeletal therapies has been limited due to toxicity (34). Current therapeutic approaches to target mechanotransduction signals in cancer work through inhibiting Rho-associated kinase (ROCK) signaling (34,35). ROCK inhibition was recently reported to suppress YAP activity in MPM cells harboring LAST2 mutation, suggesting that ROCK could regulate the Hippo pathway through a LATS2-independent mechanism (36).…”
Section: Rockmentioning
confidence: 99%